2020
DOI: 10.3390/app10041244
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Severity of Alzheimer’s Disease with Multiscale Entropy Analysis of EEG Dynamics

Abstract: Multiscale entropy (MSE) was used to analyze electroencephalography (EEG) signals to differentiate patients with Alzheimer’s disease (AD) from healthy subjects. It was found that the MSE values of the EEG signals from the healthy subjects are higher than those of the AD ones at small time scale factors in the MSE algorithm, while lower than those of the AD patients at large time scale factors. Based on the finding, we applied the linear discriminant analysis (LDA) to optimize the differentiating performance by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Fifth, this study used sample entropy [ 12 ] as the entropic metric of multiscale entropy analysis [ 10 , 34 ] to quantify EEG complexity in AD, MCI patients, and elderly controls, as widely adopted by clinical studies investigating MSE-based nonlinear analysis of EEG signals in AD [ 14 , 33 , 34 , 35 , 36 , 37 , 39 , 40 , 41 ]. This allows straightforward comparisons of the MSE results and for discussing their interpretations related to AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, this study used sample entropy [ 12 ] as the entropic metric of multiscale entropy analysis [ 10 , 34 ] to quantify EEG complexity in AD, MCI patients, and elderly controls, as widely adopted by clinical studies investigating MSE-based nonlinear analysis of EEG signals in AD [ 14 , 33 , 34 , 35 , 36 , 37 , 39 , 40 , 41 ]. This allows straightforward comparisons of the MSE results and for discussing their interpretations related to AD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been posited that this is the result of alpha slowing due to thalamocortical dysrhythmia [ 19 , 20 , 21 , 22 , 23 , 24 ]. In order to investigate changes in nonlinear intrinsic brain complexity, MSE-based analyses have been applied to resting-state EEG and MEG signals of individuals with different pathological conditions [ 9 , 25 ], such as psychiatric disorders [ 26 , 27 ], pain conditions [ 28 , 29 , 30 , 31 ], and neurological diseases [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In particular, MSE-based resting-state EEG studies in AD and dementia patients [ 33 , 34 , 35 , 36 , 37 , 39 , 40 , 41 ] have reported that at small time scales, entropy values were lower in MCI and AD patients than in healthy controls; at large time scales, entropy values tended to be higher in AD patients than in healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental evidence to support this hypothesis is limited. In this study, we are going to evaluate whether the widely utilized complexity-based metrics-MSE is sensitive and informative metric for characterizing the impact of qigong on complexity in cardiovascular and nervous systems [54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
“…MSE have advantage to measure the irregularity time series under different time scales 51 . It's designed to reflect the degree of health condition of a biological system by its output physiological signals 53 , which is particularly developed to analyze nonlinear and non-stationary constant signals, and their relationship. It has been hypothesized that as part of complexity physiologic systems, EEG and HRV have similar changing trend on the same time scale 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EEG can be used in the differential diagnosis between AD and other diseases leading to dementia, such as vascular brain damage [20,21] and Lewy body dementia [22][23][24][25][26]. Similar methodologies to the one proposed, EEG signal processing and supervised learning classification for recognizing AD patients, have been commonly used in the last decade [27][28][29]. Fiscon et al used Fourier analysis and wavelet transform to extract EEG features which then were classified by a decision trees algorithm [30].…”
Section: Introductionmentioning
confidence: 99%